Visualising M’bona religious beliefs and practices : a visual cultural artistic co-production with the custodians of Khulubvi and Associated Rain Shrines in Nsanje, Malawi - Kriel, Lize (University of Pretoria, 2025)
Thesis (PhD (Visual Studies))--University of Pretoria, 2025.